Imagery ability and imagery use in individual and team sports - Peltomäki, Ville (2014)
The purpose of this research was to examine whether individual and team sport athletes differ in their imagery use and imagery ability, and to examine whether level of sport participation or weekly sport involvement are variables that differentiate between athletes on the basis of their levels of imagery ability and imagery use. Two measures were conducted. The Sport Imagery Ability Measure (SIAM) is a 48-item self-report measure that uses four sport related scenes to examine the dimensional, sensorial, and emotional characteristics of generating images. The Sport Imagery Questionnaire (SIQ) is a 30-item self-report measure that examines five characteristics associated with the cognitive and motivational aspects of imagery use. Participants (N=207) were recruited from high schools, sport clubs and university physical education courses in Finland. The athletes completed the Finnish translations of each measure within their specific organisational settings. Analysis involved the use of independent samples t -tests to compare means from individual and team sport groups. Group comparisons revealed that individual athletes had significantly (t = -3.121, p = .002) higher means in kinaesthetic imagery ability compared to team sport athletes. This demonstrates that individual and team athletes have distinct abilities and characteristics when it comes to sport-oriented imagery. In addition, results showed significant differences in imagery use between these two groups. Score comparisons indicated that individual athletes had significantly higher use of motivation general-arousal (MG-A) (t = -2.188, p = .03) and motivation general-mastery (MG-M) ( t =-3.213, p = .002) imagery. These findings offer some indication that individual and team sport athletes employ the motivational functions of imagery differently. Motivational general arousal may be an interactive oriented type of imagery that is specifically needed in individual sports because there are no teammate to psyc you up. When comparing national and regional level athletes, it was found that national level athletes had significantly (t = 2.222, p = .027) greater visual imagery ability than regional athletes. It appears that national level athletes are able to use their visual ability more efficiently. Results also showed greater use of motivation general-mastery (MG-M) by national level athletes, which suggest that ability to visual imagery and use of general motivational-mastery skills are important characteristics in differentiating national and regional athletes from each other. Time of weekly participation in training or competing seems not to be a differentiating factor in imagery ability. Still, comparison between high and low training groups showed that imagery use of the motivational general-mastery was significantly (t = -2.236, p = 0.03) higher with high training group (29.336.0) when compared low training group (26.936.2). Overall, these initial results support the proposition that individual and team athletes have distinct abilities and characteristics when it comes to sport-oriented imagery. The information of this study may help coaches and athletes to identify the mental preparation needs of specific sports and to present additional information about individual differences in sport imagery. This knowledge can be used in designing mental imagery rehearsal programs for the purpose of enhancing physical performance.